Simulation Analysis of an ETC Monitoring and Imaging Supplementary Lighting Device for Freeways - Shijian Yin; Zhiyong Ma; Xiaojie Luo; Huayang Yu (Infrastructures)
To address the glare issues caused by highway ETC gantry monitoring and imaging illumination devices, this paper first investigates the mechanism of disability glare and derives the formula for the glare threshold increment. Subsequently, using the glare increment threshold as the evaluation metric and incorporating the current regulatory requirements for illumination devices, a simulation model for ETC gantry monitoring and imaging illumination devices was developed. A single-variable control method was applied to conduct simulation experiments on the glare problems from multiple perspectives (e.g., different standard illuminance levels, various luminous areas, varying installation heights, and different lateral offsets), and the glare level was analyzed using the glare increment threshold method. It was found that when the lateral offset of the illumination device reached 4 m, the glare increment threshold decreased by more than 50%. Additionally, it is recommended that the illuminance of the illumination device should be greater than 15 lx.